(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The current research aims the to get to know on the impact of electronic tests on the academic achievement of department students Science branch Physics/Faculty of Basic Education in University of Babylon In order to verify the aim of the research, it was formulated the two researchers the following questions:1. Are there statistically significant differences at the significance level (0.05) between the average student achievement scores in the electronic test and the traditional test? In collection Students Physics, fourth stage/ College of Basic Education / University of Babylon? 2. Is there a correlation between students’ achievement scores in the electronic test and the traditional test? Majoring in physics? useThe two researchersDescriptive approach in conducting research, And Choose grades for a course taught in an academic program at the University of Babylon in Iraq via in-person instruction for the academic year 2019-2020And electronically in the 20th academic year20-2021 The researchers relied on a research tool (statistical) that was presented to a group of arbitrators to determine its validity, and it obtained consensus from 90% of them. she:(Pearson correlation coefficient, testt-test) After applying the research tool, the researchers found that there were statistically significant differences at the 0.05 level between students’ scores in the electronic and traditional test. In light of the research results, the researchers reached a set of conclusions, recommendations and proposals.